Invasive Aspergillosis Following Dengue: An Autopsy Case and Review of the Literature - Avichal Rajpal; Immanuvel Jebaraj; Inderpaul Singh Sehgal; Kritarth Rathi; Sangamitra Rajasekaran; Uma Nahar; Kuruswamy Thurai Prasad; Shivaprakash M. Rudramurthy; Ritesh Agarwal; Valliappan Muthu (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Invasive aspergillosis typically occurs in immunocompromised hosts but has been increasingly recognized following viral illnesses, including dengue and coronavirus disease 2019. Herein, a fatal case of disseminated aspergillosis following severe dengue is described, and the association is systematically reviewed. A previously healthy 25-year-old woman presented with fever and multiorgan dysfunction. Dengue IgM results were positive, and other tropical infections were excluded. Despite intensive care, the patient developed progressive respiratory failure, refractory shock, and acute kidney injury and died. An autopsy revealed diffuse alveolar damage and extensive invasive aspergillosis involving the bronchi, pulmonary vasculature, and myocardium. In the present systematic review, 21 additional cases of invasive aspergillosis following dengue (total n = 22; median age 36 years, 59% male) were identified, predominantly in Asia. Fifteen cases (68%) had pulmonary involvement. Most patients had severe dengue with multiorgan dysfunction. The overall mortality was 63.6%; 23% of cases were diagnosed postmortem. Invasive aspergillosis complicating severe dengue broadens the spectrum of viral-associated aspergillosis.